The influence of Western classical singing method on the 21st century Chinese national vocal music / Sun Jing Jing - Sun , Jing Jing (2019)
This research aims to investigate the integration of Western classical singing methods in China’s national vocal music. The research is in the field of vocal pedagogy, particularly on Western classical singing and the development of Chinese national vocal music. This research includes the analysis of the Western and Chinese classical singing methods, the historical analysis of the influence of Western classical singing on Chinese national vocal music, and the case study of the Chinese famous lyric soprano Wu Bixia, the pioneer on the integration of Western classical singing methods on the Chinese national vocal music. In the art of singing, there are many similarities in Chinese and Western vocal music (specifically with the new Nazionale cantanti and bel canto), and this research will analyze Wu Bixia’s singing methods and her theory of integrating Western classical singing into Chinese vocal music.